2021
DOI: 10.51327/wcuo5792
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Religious Orientation and PsyCap in Mitigating Technostress

Abstract: The government's work from home policy because of COVID-19 Pandemic has had an impact on changing the learning system. This policy necessitates that students use technology to carry out learning activities. This causes the individual to experience difficulties. The digitization of learning activities has an impact on mental health problems such as technostress. Technostress refers to a modern adaptation disease caused by an inability to cope with new technology. The level of technostress of each individual var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In contrast, the study of (Raza et al 2022) showed that optimism is a contributory factor to the negative effects of stress caused by new technologies. In the same vein, the study of (Wijayanti and Riza 2021) demonstrated that the elements that characterize the construct of psychological capital (self-efficacy, optimism, resilience, and hope) can activate behaviors that contribute to reducing the effects of technostress. Again, due in part to the exceptional situation caused by the pandemic, there appear to be few studies of students, so the in-depth study conducted as part of the survey shows that optimism can be considered a personal resource and protective factor.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the study of (Raza et al 2022) showed that optimism is a contributory factor to the negative effects of stress caused by new technologies. In the same vein, the study of (Wijayanti and Riza 2021) demonstrated that the elements that characterize the construct of psychological capital (self-efficacy, optimism, resilience, and hope) can activate behaviors that contribute to reducing the effects of technostress. Again, due in part to the exceptional situation caused by the pandemic, there appear to be few studies of students, so the in-depth study conducted as part of the survey shows that optimism can be considered a personal resource and protective factor.…”
Section: Discussionmentioning
confidence: 98%